Récits de vie et qualité paysagère : le point de vue de jardiniers - Patricia Brulon-Le Crenn (Projets de Paysage)
Environmental quality can be grasped in two different analyses. The first one would be implemented in landscape projects and call for the mobilization of a shared subjectivity among all the parties involved in planning. Material elements of the country or environmental patterns making reference to rural structures would be used as criteria for assessment. These contemporary views would show the willingness to enhance new types of areas, with standards of assessment deeply marked by environmental values. The second one, individual and subjective, asks to face, of one’s own, a place, to understand the sensitive aspect of a territory, through a particular actor’s speech. From interviews made in Breton Departments of open spaces, gardeners’ life accounts give an interesting account on the used criteria, to assess and judge the environmental quality of alternative areas which, henceforth, are spread in town. It would seem that the job perception and the environmental concerns are in conflict on perceptual schemata of the environmental quality. The concept of “a well-done job” would remain one of the main filters of analysis.